Nitric Oxide Affects Rice Root Growth by Regulating Auxin Transport Under Nitrate Supply - Sun, Huwei; Feng, Fan; Liu, Juan; Zhao, Quanzhi (Frontiers in Plant Science, 2018)
Nitrogen (N) is a major essential nutrient for plant growth and development, and an important food crop globally. Although ammonium (NH4+) is the main N source for rice, nitrate (NO3-) is also absorbed and utilised. Rice responds to NO3- supply by changing root morphology. However, the mechanisms of rice root growth and formation under NO3- supply are unclear. Nitric oxide (NO) and auxin are important regulators of root growth and development under NO3- supply. How the interactions between NO and auxin regulate root growth in response to NO3- are unknow. In this study, the levels of indole-3-acetic acid (IAA) and NO in roots, and the responses of lateral roots (LRs) and seminal roots (SRs) to NH4+ and NO3-, were investigated using wild-type (WT) rice, as well as osnia2 and ospin1b mutants. NO3- supply promoted LR formation and SR elongation. The effects of NO donor and inhibitor/scavenger supply on NO levels and the root morphology of WT and nia2 mutants under NH4+ or NO3- suggest that NO3--induced NO is generated via the nitrate reductase (NR) pathway rather than the NO synthase (NOS)-like pathway. IAA levels, [3H] IAA transport, and PIN gene expression in roots were enhanced under NO3- relative to NH4+ supply. These results suggest that NO3- regulates auxin transport in roots. Application of SNP under NH4+ supply, or of cPTIO under NO3- supply, resulted in auxin levels in roots similar to those under NO3- and NH4+ supply, respectively. Compared to WT, the roots of the pin1b mutant had lower auxin levels, fewer LRs, and shorter SRs. Thus, NO affects root growth by regulating auxin transport in response to NO3-. Overall, our findings suggest that NO3- influences LR formation and SR elongation by regulating auxin transport via a mechanism involving NO.